Parodontoprotective action of flavan- and lecithincontent hepatoprotectors on rats, which received the peroxide sunflower oil - A. I. Furdychko (Kazimierz Wielki University, 2017)
The aim. To determine parodontoprotective action of flavan- and lecithincontent hepatoprotectors on rats, which received the peroxide sunflower oil The materials and methods. Quertulin (quercetin + inulin + citrate Ca), lekvin (lecithin + quercetin + inulin + Ca citrate) and lekasil (lecithin + flavolignan from Silybum marianum + Ca citrate) were used in doses 300 mg/kg every day during last 45 days. The peroxide sunflower oil introduced in dose 1 ml/rat every day during 75 days. The activity elastase, urease, catalase, lysozyme and content of malonic dialdehide (MDA) were determined in gingiva. The findings. The inflammation and dysbiosis were developed into rat gingiva, which received the peroxide sunflower oil, but the activities of catalase and lysozyme were reduced. The introduction of quertulin, lekvin and lekasil reduced inflammation and dysbiosis, but raised the activities catalase and lysozyme. Conclusion: The flavan- and lecithincontent means possess parodontoprotective action.